Circadian clock network desynchrony promotes weight gain and alters glucose homeostasis in mice - Isa Kolbe; Brinja Leinweber; Matthias Brandenburger; Henrik Oster (Elsevier, 2019)
Objective: A network of endogenous circadian clocks adapts physiology and behavior to recurring changes in environmental demands across the 24-hour day cycle. Circadian disruption promotes weight gain and type 2 diabetes development. In this study, we aim to dissect the roles of different tissue clocks in the regulation of energy metabolism. Methods: We used mice with genetically ablated clock function in the circadian pacemaker of the suprachiasmatic nucleus (SCN) under different light and feeding conditions to study peripheral clock resetting and the role of the peripheral clock network in the regulation of glucose handling and metabolic homeostasis. Results: In SCN clock-deficient mice, behavioral and non-SCN tissue clock rhythms are sustained under rhythmic lighting conditions but deteriorate quickly in constant darkness. In parallel to the loss of behavioral and molecular rhythms, the animals develop adiposity and impaired glucose utilization in constant darkness. Restoring peripheral clock rhythmicity and synchrony by time-restricted feeding normalizes body weight and glucose metabolism. Conclusions: These data reveal the importance of an overall synchronized circadian clockwork for the maintenance of metabolic homeostasis. Keywords: Body weight, Constant darkness, Suprachiasmatic nucleus, Circadian clock, Glucose metabolism, Light-dark cycle